Backscatter amplification effect for a reflected partially coherent Gaussian beam in turbulent medium. (September 2015) - Xiang, Ning-Jing; Wu, Zhen-Sen; Guo, Qiu-Fen; Wang, Ming-Jun
Abstract: The extended Huygens–Fresnel principle is used to develop a formulation for the backscattered intensity enhancement of a Gaussian Schell-model source beam through a weak turbulence. The results are shown that backscattered intensity enhancement factor of the reflected GSM beam is concerned with the coherence length of source, the wavelength, the size of target and wave structure function. In addition, the closed-form expressions can interpret backscattered intensity enhancement of plane and spherical wave scattered from a diffuse target. The results are illustrated by examples and compared with the previous work. Highlights: The Gaussian Schell-model beam is considered. The size of target is discussed. The results can interpret the enhancement effect of plane and spherical wave.